The implementation of outdoor classroom based program in UPM - Md Sahak, Siti Nabihah; Roslan, Samsilah; Ma'rof, Aini Marina (2017)
Outdoor classroom is widely implemented in western countries such as United States, United Kingdom and Switzerland. By giving students the opportunity to get outside and experience the nature all by themselves, they can bring the beauty of learning to life. The goodness of outdoor-based learning, which includes on-site learning and hands-on activities, can be implemented as a form of informal learning. In outdoor classroom, experiential learning happens when learning occurs at various places rich in information such as green houses, museums, botanical gardens etc. Hence, this paper tends to discuss the concept of outdoor classroom conducted in Universiti Putra Malaysia (UPM) called eDU-PARK where school students visit and learn about science, technology and innovations at designated places in the university. Hence, experiential learning theory will be used to explain further about the concept of outdoor classroom.